2018
DOI: 10.2147/cia.s156044
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes mellitus: distribution of genetic markers in Kazakh population

Abstract: BackgroundEthnic differences exist in the frequencies of genetic variations that contribute to the risk of common disease. This study aimed to analyse the distribution of several genes, previously associated with susceptibility to type 2 diabetes and obesity-related phenotypes, in a Kazakh population.MethodsA total of 966 individuals belonging to the Kazakh ethnicity were recruited from an outpatient clinic. We genotyped 41 common single nucleotide polymorphisms (SNPs) previously associated with type 2 diabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…More recently, a number of 41 genes previously associated with T2D and obesity were studied in a Kazakh population [38]. The results indicated that some of these SNPs might have a considerable effect on the predisposition to development of diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, a number of 41 genes previously associated with T2D and obesity were studied in a Kazakh population [38]. The results indicated that some of these SNPs might have a considerable effect on the predisposition to development of diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies based on historical and genetic data have suggested that the Kazakh population was formed as a result of admixture of European and Asian populations [27]. Comparative analysis of allelic frequencies of the studied SNPs showed significant differences between the Kazakh population and the majority of other population groups from the 1000 Genome project database.…”
Section: Discussionmentioning
confidence: 96%
“…The Kazakh population is the indigenous population of the Republic of Kazakhstan, which is located between Europe and Asia. The geographic location of the Republic of Kazakhstan for numerous centuries has contributed to the formation of a specific gene pool, which is different from the genetic pools of other populations ( 13 ). A recent study reported that the Kazakh population was anthropologically similar to the Mongoloid ethnicity, and they have an intermediate position between the Caucasian and Asian populations ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…The geographic location of the Republic of Kazakhstan for numerous centuries has contributed to the formation of a specific gene pool, which is different from the genetic pools of other populations ( 13 ). A recent study reported that the Kazakh population was anthropologically similar to the Mongoloid ethnicity, and they have an intermediate position between the Caucasian and Asian populations ( 13 ). Moreover, allelic frequency distributions of 22 autosomal short tandem repeats in the Kazakh population differ from Han, Xinjiang, Kyrgyz and Xibe populations, but are similar to the Uyghurs ( 14 ).…”
Section: Introductionmentioning
confidence: 99%